1983
DOI: 10.1128/iai.42.1.202-207.1983
|View full text |Cite
|
Sign up to set email alerts
|

Effect of parenteral immunization on the local immunoglobulin A response of the intestine to Shigella flexneri antigens

Abstract: Most traditional methods of immunization involve parenteral vaccines. Using a chronically isolated ileal loop model as the probe, we examined the effect of a primary parenteral immunization on the local immune response of the intestine. Secretions from isolated ileal loops of rabbits given a primary parenteral immunization with Shigella flexneri without adjuvant showed a small, but definite, specific immunoglobulin A (IgA) response locally, whereas a vigorous serum antigen-specific IgG response was elicited. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

1985
1985
1998
1998

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…In all of the above groups, no or trivial amounts of IgG anti-shigella LPS were found in either serum or intestinal secretions. This lack of IgG in intestinal secretions after oral immunization was consistent with our previous studies (15,16) and is not due to the instability of IgG in the isolated ileal loops (19 Shedding of live bacteria. Loop fluids and stool samples were cultured on MacConkey agar plates to detect shedding of shigellae as described previously (17).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In all of the above groups, no or trivial amounts of IgG anti-shigella LPS were found in either serum or intestinal secretions. This lack of IgG in intestinal secretions after oral immunization was consistent with our previous studies (15,16) and is not due to the instability of IgG in the isolated ileal loops (19 Shedding of live bacteria. Loop fluids and stool samples were cultured on MacConkey agar plates to detect shedding of shigellae as described previously (17).…”
Section: Resultssupporting
confidence: 92%
“…A previous study from our laboratory has indicated that to achieve an enhanced local IgA memory response to Shigella flexneri, oral immunization is effective, but parenteral immunization (without adjuvant) is not (19). Others have found that parenteral immunization may actually suppress the subsequent local immune response to the same antigen (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Some workers have employed combinations of parenteral injections of antigen and oral stimulation (6,20,29). Most often, priming of animals by parenteral immunization several days to weeks before mucosal stimulation has been ineffec-tive in enhancing mucosal immunity (17,40). A notable exception is the use of intraperitoneal priming, which probably causes some direct stimulation of mucosal immunity (26,27).…”
mentioning
confidence: 99%
“…The presence of specific IgG immunoglobulins and the lack of specific IgA immunoglobulins in the milk of vaccinated dams was rather unexpected since parenteral immunization with other enteric organisms had previously led to production of a specific IgA as well as IgG response (Keren et al 1983). The ELISA assay used in this study detected low amounts of specific IgA immunoglobulins in the positive control wells, which seems to indicate a true absence of specific IgA immunoglobulins in the milk of vaccinated dams.…”
Section: Discussionmentioning
confidence: 51%